PEMETAAN BATHIMETRI MENGGUNAKAN SINGLEBEAM ECHOSOUNDER DI PERAIRAN PULAU SALI KABUPATEN HALMAHERA SELATAN - Gusman, Putri Zakia; Jaya, Yales Veva; Febrianto, Try (Dinamika Maritim, 2018)
Bathymetry is a measurement for the deepness of sea. The Sali Island are one of the destinations island for sightseeing, which means that there are many ships or speedboats passing through to escort tourists. The purpose of this study was to map the bathymetry of Sali Island’s waters based on the results of singlebeam echosounder measurements in the form of 2D and 3D maps. Bathymetric mapping is done in the Sali Island’s waters, South Halmahera Regency on 7-25 March 2017.Bathymetry data is obtained from singlebeam echosounder MK III measurements that were corrected for tidal values. Tides are analyzed using the Admiralty method. Data was processed using MapInfo Professional 10 software, Surfer 11. Based on this study, the depth of Sali Island’s waters ranged from 20-260 m which had a diverse seabed shape that was sloping and steep with mixed tidal types inclined to double daily.